2021
DOI: 10.1186/s13012-021-01090-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of evidence-based practice implementation in drug and alcohol settings: applying the consolidated framework for implementation research framework

Abstract: Background There is a paucity of translational research programmes to improve implementation of evidence-based care in drug and alcohol settings. This systematic review aimed to provide a synthesis and evaluation of the effectiveness of implementation programmes of treatment for patients with drug and alcohol problems using the Consolidated Framework for Implementation Research (CFIR). Methods A comprehensive systematic review was conducted using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…This is an important distinction, since findings from the field of implementation science consistently demonstrate that the implementation process itself also has implications for implementation outcomes (9,10). A recent systematic review of evidence-based practise implementation in AOD settings found that only two of the twenty included studies employed a comprehensive implementation framework, and no included studies focused on treating comorbidity (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important distinction, since findings from the field of implementation science consistently demonstrate that the implementation process itself also has implications for implementation outcomes (9,10). A recent systematic review of evidence-based practise implementation in AOD settings found that only two of the twenty included studies employed a comprehensive implementation framework, and no included studies focused on treating comorbidity (11).…”
Section: Introductionmentioning
confidence: 99%
“…It includes five domains of influence derived from a consolidation of the plethora of terms and concepts generated by implementation researchers: (1) intervention characteristics (e.g., evidence strength and quality, adaptability), (2) outer setting (e.g., patient needs and resources, external policies and incentives), (3) inner setting (e.g., implementation climate, readiness for implementation), (4) individuals involved (e.g., self-efficacy, knowledge, and beliefs about the intervention), and (5) the implementation process (e.g., engaging members of the organisation, executing the innovation). No previous studies have systematically evaluated barriers and facilitators of implementation of comorbidity training according to a validated framework, which is key to refining ongoing training programs and future roll out efforts (11).…”
Section: Introductionmentioning
confidence: 99%
“…This could add to the quality of publications in many ways: "using adequate research frameworks and models helps research studies to frame study questions and hypotheses, link to important background literature, clarify constructs to be measured, depict relationships to be tested and contextualize results, they provide a common language and thus allow to advance and develop cumulative evidence" (Birken et al, 2017). A recent systematic review has proved the utility of applying comprehensive implementation frameworks in implementation research (Louie et al, 2021).…”
mentioning
confidence: 99%
“…From a theoretical perspective, social cognitive theories have been widely used to explain health-related behaviours of individuals [12]. Although very little research has applied social cognitive theories to the study of health practitioner behaviour [13], research evaluating EBP implementation in drug and alcohol settings has often been guided by the assumption that clinician factors have an important relationship to implementation delity [14]. Clinician factors most frequently measured in such studies include demographics (e.g.…”
mentioning
confidence: 99%
“…Organisational change theories such as Rogers' [31] diffusion of innovations theory have also highlighted the importance of clinician perceptions of the capacity of their organisation to support and implement new innovations, and drug and alcohol clinician perceptions of factors related to their organisational context have been evaluated as a possible mediator of implementation delity [15]. While clinician demographics have frequently been included in studies investigating factors related to implementation delity in drug and alcohol contexts, signi cant relationships are not often found [14]. Some studies have indicated that higher levels of education are associated with higher delity [15], that this distinction is sometimes no longer present following training [25], and that clinicians with lower levels of education can demonstrate greater increases in implementation delity following training [16].…”
mentioning
confidence: 99%